2001
DOI: 10.1182/blood.v98.8.2482
|View full text |Cite
|
Sign up to set email alerts
|

HIV gp120 receptors on human dendritic cells

Abstract: Dendritic cells (DCs) are important targets for human immunodeficiency virus (HIV) because of their roles during transmission and also maintenance of immune competence. Furthermore, DCs are a key cell in the development of HIV vaccines. In both these settings the mechanism of binding of the HIV envelope protein gp120 to DCs is of importance. Recently a single C-type lectin receptor (CLR), DC-SIGN, has been reported to be the predominant receptor on monocyte-derived DCs (MDDCs) rather than CD4. In this study a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
170
4
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 43 publications
4
170
4
2
Order By: Relevance
“…Together with other C-type lectins on the surface of dendritic cells, DC-SIGN appears as a key player in the initial stages of HIV infection through its ability to capture and transfer virus to T lymphocytes (45). DC-SIGN is found in both peripheral blood dendritic cell precursors and mucosal dendritic cells and is therefore adequately positioned for HIV spread both after sexual transmission and after contamination with blood.…”
Section: Discussionmentioning
confidence: 99%
“…Together with other C-type lectins on the surface of dendritic cells, DC-SIGN appears as a key player in the initial stages of HIV infection through its ability to capture and transfer virus to T lymphocytes (45). DC-SIGN is found in both peripheral blood dendritic cell precursors and mucosal dendritic cells and is therefore adequately positioned for HIV spread both after sexual transmission and after contamination with blood.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that myeloid and lymphoid precursor DC subsets in blood lack DC-SIGN expression. 20,21 We set out to investigate the expression of DC-SIGN by human blood mononuclear cells. Initial experiments showed the presence of a small population of cells (0.02% of total PBMCs) that expressed DC-SIGN and that could be visualized by direct staining in human blood ( Figure 1A).…”
Section: Isolation and Characterization Of Dc-sign-expressing Cells Imentioning
confidence: 99%
“…19 In recent studies, it was demonstrated that DC-SIGN is not expressed by plasmacytoid DCs, by myeloid blood precursor DC subsets, or by monocytes. 3,20,21 However, these DC subsets were purified by depletion of CD14 ϩ cells, which included monocytes. We observed that upon in vitro culture, DC-SIGN expression is rapidly induced in CD14 ϩ monocytes, indicating that a DC-SIGN ϩ precursor DC might coexpress CD14.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 binds to DCs. However, the identity of the HIV-1 receptors on DCs is currently under intense debate (11)(12)(13)(14)(15). Different receptors have been demonstrated to interact with HIV-1 on DCs, such as the C-type lectin DC-SIGN (11,16), the mannose receptor (17), langerin (18), and CD4 (17).…”
mentioning
confidence: 99%